2013
DOI: 10.1080/13657305.2013.747224
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood Capabilities and Pathways of Shrimp Farmers in the Mekong Delta, Vietnam

Abstract: & Shrimp farming is a major livelihood activity in the Mekong Delta in the southernmost part of Vietnam. The Vietnamese government has promoted shrimp farming as a way to reduce poverty, provide employment opportunities and increase exports to support economic development. The shrimp farming system, however, is economically and ecologically risky and may negatively influence the environment and the sustainability of local people's livelihoods. Because very little is known about the diversity of strategies peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 29 publications
3
59
1
Order By: Relevance
“…Sixty-five percent of the parents did not want their children to become fishers, and 54% of households considered their livelihood worse than it was 10 years ago. Although the mean annual net income per household of approximately VND 40 million (USD 2300) was not lower and even higher than that from aquaculture (VND 34 million) [46], fishers were not satisfied with their job because of the high risks and uncertainties. Fishing villages are usually located in distant areas with little access to education and alternative job opportunities.…”
Section: Fishery Livelihood Sustainabilitymentioning
confidence: 99%
“…Sixty-five percent of the parents did not want their children to become fishers, and 54% of households considered their livelihood worse than it was 10 years ago. Although the mean annual net income per household of approximately VND 40 million (USD 2300) was not lower and even higher than that from aquaculture (VND 34 million) [46], fishers were not satisfied with their job because of the high risks and uncertainties. Fishing villages are usually located in distant areas with little access to education and alternative job opportunities.…”
Section: Fishery Livelihood Sustainabilitymentioning
confidence: 99%
“…This shows that farmers value the ecological services of mangroves together with the economical return expected from this farming method. In terms of multifuctionality, Ha et al () report that the majority of mangrove–shrimp farmers in Nam Can district reported that mangroves play an important role in maintaining ecological function and thus in the success of shrimp farming. Also, harvests other than tiger shrimp diversify their livelihood for both market and subsistence purposes, at a lower cost than other methods.…”
Section: Discussion: the Role Of Multifunctionality In Agrarian Transmentioning
confidence: 99%
“…Even though when mangroves get to year 11 or older they can be harvested (Ha et al , ), the calculation of benefit sharing between forestry companies and shrimp farmers is unclear and unfair (Ha et al , , ). Thus farmers sometimes cut some mangrove or do not care about the quality of the mangrove forest (Ha et al , , ). Farmers are also concerned that mangroves occupy too much of the water surface that could otherwise be used for shrimp farming or that older mangroves do not provide effective habitat for shrimp (Ha et al , ).…”
Section: Case Study: the First Organic Shrimp Project In Vietnammentioning
confidence: 94%
“…Despite its distance from major commercial and industrial centers, the village represents well the legacy of rapid economic development that has transformed much of rural, coastal Vietnam (Ha et al. ; Thu and Populus ).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Dông Hải Commune is a fairly isolated village in Duyên Hải District, 70 kilometers from the provincial capital, TràVinh, and about 275 kilometers from the commercial center of Vietnam, Ho Chi Minh City (Figure 1). Despite its distance from major commercial and industrial centers, the village represents well the legacy of rapid economic development that has transformed much of rural, coastal Vietnam (Ha et al 2013;Thu and Populus 2007).…”
Section: Site Descriptionmentioning
confidence: 99%